KEPENTINGAN POLITIK DAN EKONOMI KEPALA DAERAH DALAM REFORMASI BIROKRASI : Kasus Reformasi Pelayanan Perizinan Di1Kabupaten Gowa Dan Kabupaten Takalar - Prianto, Andi Luhur (Jurnal Borneo Administrator, 2012)
The design of decentralization has given specific space for government bureaucracy to create and innovation the acceleration of development territory. At this point in the required skills apparatuses with forward thinking to achieve a professional bureaucracyin an institutional mechanism that is efficient, effective and equity. Institutional arrangement bureaucracyis not geared to improve the quality of public services, but in order to accommodate the practice of politicization of bureaucracy in perpetuating oligarchy of power head area. The purpose of this study to answer the questions: (1.) How is the actual picture of the practice of bureaucratic reform licensing services in Gowa and Takalar regency, (2.) What is the connection the interests of regional heads in bureaucratic reform licensing services in Gowa and Takalar regency. The reserach aimed that the licensing service reforms under taken by the local government, Gowa and Takalar Regency likely still partial, in which the reform is based on the basic needs and regulatory pressure center. Orientation of the provision of services also permit limited to the normative aspect alone. In both regions, the character possessed strong leadership allows the behavior of the regional head office personnel licensing services oriented to meet the political and economic objectives of the head region.  Keywords : bureaucratic reform, local, services, licensingDesain desentralisasitelah memberi ruang gerak yang spesifik kepada birokrasi pemerintah daerah untuk berkreasi dan berinovasi dalam akselerasi pembangunan diwilayahnya. Pada posisi ini dituntut kemampuan Sumber DayaAparatur dengan visi yang jauh kedepan (forward thinking) untuk mewujudkan profesionalisme birokrasi dalam sebuah mekanisme kelembagaan yang efisien, efektif dan berkeadilan (equity).Penataan kelembagaan birokrasi bukan diarahkan untuk meningkatkan kualitas pelayanan publik, tetapi demi mengakomodasi praktek politisasi birokrasi dalam melanggengkan oligarki kekuasaan kepala daerah. Tujuan penelitian ini untuk menjawab pertanyaan : (1).Bagaimanakah gambaran aktual tentang praktek reformasi birokrasi pelayanan perizinan di Kabupaten Gowa dan Kabupaten Takalar, (2.) Bagaimanakah kaitan kepentingan-kepentingan kepala daerah dalam reformasi birokrasi pelayanan perizinan di Kabupaten Gowa dan Kabupaten Takalar? Hasil penelitianmenujukkan bahwa reformasi pelayanan perizinan yang dilakukan oleh pemerintah daerah, yakni kabupaten Gowa dan Kabupaten Takalar cenderung masih parsial, di mana reformasi dilandasi atas dasar kebutuhan dan desakan peraturan pusat. Orientasi penyelenggaraan pelayanan perizinan juga hanya terbatas pada aspek normatif semata.Pada kedua daerah ini, karakter strong leadership yang dimiliki kepala daerah memungkinkan perilaku aparatur kantor pelayanan perizinan diorientasikan untuk memenuhi tujuan politik dan ekonomi sang kepala daerah.  Kata kunci: reformasi birokrasi, daerah, pelayanan, perizinan